2016
DOI: 10.1002/smr.1787
|View full text |Cite
|
Sign up to set email alerts
|

EXACT: A tool for comprehending VBA-based Excel spreadsheet applications

Abstract: Spreadsheet applications are widely adopted by millions of end users from several application domains and provide strategic support to many business, scientific, industrial, and organizational processes. These applications are usually developed by rapid application development processes, exploiting host scripting languages allowing the basic spreadsheets to provide complex functionality, business rules, and user interfaces. Several factors complicate the comprehension of these applications because they are usu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…To limit the impact on the existing tools, the integration architecture may rely on “adapter” connectors that enable a not invasive interconnection among the tools. In this step, reverse engineering processes, involving either the data produced by the tools() or the tool user interfaces, may have to be carried out. In these cases, data wrapping or tool wrapping techniques() may have to used to design the needed connectors.…”
Section: Improving Traceability Links Management Through Tool‐integramentioning
confidence: 99%
See 1 more Smart Citation
“…To limit the impact on the existing tools, the integration architecture may rely on “adapter” connectors that enable a not invasive interconnection among the tools. In this step, reverse engineering processes, involving either the data produced by the tools() or the tool user interfaces, may have to be carried out. In these cases, data wrapping or tool wrapping techniques() may have to used to design the needed connectors.…”
Section: Improving Traceability Links Management Through Tool‐integramentioning
confidence: 99%
“…Eventually, to extract the testing results, we had to develop an Excel Adapter component for retrieving information from Excel spreadsheet files. We exploited the reverse engineering process proposed in Amalfitano et al and the tool reported in Amalfitano et al for inferring the data models of the test case and the test case result artifacts stored in spreadsheet files. These models were needed for importing the data in the ALM platform.…”
Section: Using the Proposed Process In A Real Automotive Industrial Cmentioning
confidence: 99%
“…The derived model is visualized as a UML class diagram. Another interesting work of Amafitano et al [39] presents a tool that helps to analyze connections of cells and VBA code.…”
Section: Related Workmentioning
confidence: 99%